Analysis of Optimal Portfolio Formation Using Multi-Objective Optimization Method and Nadir Compromise Programming - Randa Resvitasari Aliwu; Emli Rahmi; Agusyarif Rezka Nuha; Lailany Yahya; Djihad Wungguli; Armayani Arsal (Jambura journal of mathematics, 2025)
A portfolio is a collection of financial assets in the stocks owned by a company or individual. An optimal portfolio is a selected portfolio that aligns with the investor's preferences, drawn from a set of efficient portfolios that have been formed. This research aims to create an optimal portfolio using the Multi-Objective Optimization method and the Nadir Compromise Programming (NCP) method. Additionally, Value at Risk (VaR) analysis is applied to determine the maximum risk an investor will bear for the portfolio. The data used consists of closing stock prices on the IDX30 Index from February 2022 to July 2023. The findings indicate that the optimization approach produces portfolios that align with investor risk-return preferences. The comparison of Multi-Objective Optimization and NCP methods provides insights into their effectiveness in portfolio selection. Furthermore, the VaR analysis helps investors understand potential risk levels, offering a comprehensive perspective on portfolio performance.